Desain Penguncian Pintu Perlintasan Sebidang Jenis Manual Operation Pln-Power Menggunakan Elektromagnet - Rachman, Natriya Faisal; Darmawan, Arief; Imami, Fandhi Dwi (Politeknik Perkeretaapian Indonesia Madiun, 2018)
A level crossing is a level crossing between a railroad track and a highway. In conditions on the ground, road users often violate their way through crossing lintels. The purpose of this research is to create a locking system using electromagnets and warning sound indications in order to hold the doorstop so that it cannot be lifted manually by violators who will break through the crossing doorstop. This study consists of several stages, namely the analysis of the needs of the components making tools, the process of making tools, testing tools, and analyzing test result data. The components used in this research are Ultrasonic Sensor, Infrared Sensor, Voice Recorder Module, Relay, Amplifier, Speaker Horn, and Electromagnetic Circuits. All tool designs are able to activate the Electromagnet circuit when the crossing door arm position is 30 cm from the sensor, and are able to activate the warning sound indication when the crossing door arm is lifted manually